The effectiveness of interventions to reduce informality in low- and middle-income countries - Jonas Jessen; Jochen Kluve (World Development, 2021)
Labor markets in low- and middle-income countries are characterized by high levels of informality. A multitude of interventions have been implemented to increase the formalization of firms and workers, including information campaigns, simplified registration procedures, reductions of payroll taxes, and interventions enforcing formalization. We compile a database of 170 impact estimates from 38 academic studies that evaluate empirically one or more of these formalization interventions. The quantitative analysis correlates the impact estimates of the studies—given as a measure of sign and statistical significance, the effect size or percent impacts—with explanatory factors such as intervention type, outcome variable, scope of the intervention, and contextual factors such as study design and economic context. Several key findings emerge: first, tax incentives are a particularly effective intervention type, and information interventions constitute an important component to combine with other interventions. Second, the outcome “worker registration” shows significantly better results than other outcomes. Third, large-scale policies are more effective on average than singular programs. Fourth, interventions tend to be more effective in a more promising (labor) market context.
Keywords: 330; Formalization; Firm registration; Labor registration; Impact evaluation; Low- and middle-income countries